Statistical analysis of motivators in the Serbian banking sector - Janovac, Tatjana; Simeunovi?, Ivana; Virijevic Jovanovic, Saša; Nedovi?, Nemanja; Tomi?, Gordana (Journal of Eastern European and Central Asian Research (JEECAR), 2021)
Starting from the fact that motivation presents an important factor that directly affects employee effectiveness, this paper examines the attitudes of employees regarding the ability of their leaders and managers to apply appropriate motivators in the work process. The empirical research was based on a sample of 117 respondents who were employed in the Serbian banking sector. The application of statistical methods supported by SPSS software provided the analysis of three groups of motivators applied by leaders and managers, which included material, non-monetary and work-related motivators. In addition, we examined the relationship between the length of service and respondents’ attitudes regarding the ability of leaders and managers to involve employees in the decision-making and goal-setting process. Testing hypothesis H1 using the Wilcoxon signed-rank test showed the existence of a pronounced ability of leaders and managers to motivate employees by applying material, non – monetary and work-related motivators. Testing hypothesis H2 using Spearman’s Correlation Test indicated a correlation between the studied variables at the population level. The findings of the empirical research can contribute to better efficiency and effectiveness of the operations in the banking sector.